The centrality of meaning-making in transformational learning: How HIV positive adults make sense of their lives - Bradley Courtenay; Sharan B. Merriam; Patricia M. Reeves (Adult Education Research Conference, 1996)
The meaning-making process, so central to transformational learning, is not well delineated in the literature. The purpose of this study was to understand how meaning is constructed in the lives of those diagnosed as HIV positive. Data analyzed from interviews with 18 men and women revealed that after an initial reaction period, a catalytic experience sets in motion a three-phase process of reflection and activity.